2022
DOI: 10.33448/rsd-v11i9.31981
|View full text |Cite
|
Sign up to set email alerts
|

Química Verde no Ensino de Química: Uma revisão entre 2011 e 2021 a partir de periódicos científicos

Abstract: A Química Verde, através de seus princípios, no ensino busca a formação cidadã, além do aprofundamento no conteúdo de Química. Logo, esse trabalho teve como objetivo verificar como se dá a abordagem da Química Verde no ensino de Química para o nível médio, através de uma Revisão Sistemática da Literatura. Na pesquisa bibliográfica, foi produzido um protocolo de pesquisa, utilizando-se critérios de inclusão e exclusão, com a seleção dos artigos feita nas bases de dados Google acadêmico e portal CAPES. Os result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The research indicated a noticeable growth in these two periods: an average of 2.8 publications per year until 2017 and 5.5 publications per year in the updated period. Moreira, Aires and Lorenzetti (2017) also investigated the relationship between GC and STS approach in chemistry education, arguing they contribute to minimize environmental problems and provide students with opportunities to critical thinking, making them capable of positioning themselves in the face of problems relating to the environment In a recent study, Melo and Souza (2022) discussed the approach of GC education in Brazilian high school level, based on the selection of 18 articles published from 2011 to 2021 in renowned journals using the combination of the keywords "green chemistry" and "education". The authors highlight the scarcity of works focused on the high school level, alerting that didactic strategies and tools do not use all possibilities of GC approaches, but present only illustrative experiments for the application of GC principles and adaptation of traditional laboratory practices to match GC.…”
Section: The Presence Of Green Chemistry In Chemist Education and Che...mentioning
confidence: 99%
See 1 more Smart Citation
“…The research indicated a noticeable growth in these two periods: an average of 2.8 publications per year until 2017 and 5.5 publications per year in the updated period. Moreira, Aires and Lorenzetti (2017) also investigated the relationship between GC and STS approach in chemistry education, arguing they contribute to minimize environmental problems and provide students with opportunities to critical thinking, making them capable of positioning themselves in the face of problems relating to the environment In a recent study, Melo and Souza (2022) discussed the approach of GC education in Brazilian high school level, based on the selection of 18 articles published from 2011 to 2021 in renowned journals using the combination of the keywords "green chemistry" and "education". The authors highlight the scarcity of works focused on the high school level, alerting that didactic strategies and tools do not use all possibilities of GC approaches, but present only illustrative experiments for the application of GC principles and adaptation of traditional laboratory practices to match GC.…”
Section: The Presence Of Green Chemistry In Chemist Education and Che...mentioning
confidence: 99%
“…Thus, there have been several efforts by many researchers to establish an overview of GC and its education in the Brazilian context, through bibliographic research in different databases and under different inclusion criteria. However, what is perceived is that the scope of analysis ends up being limited when a single database is searched and, consequently, a reduced number of works is identified (PITANGA; SANTOS; FERREIRA, 2017; BRANDÃO et al, 2018;MELO;SOUZA, 2022). Therefore, this work aimed to perform a comprehensive literature review for characterizing the contributions of research on GC education in Brazil, based on publications by Brazilian authors.…”
Section: The Presence Of Green Chemistry In Chemist Education and Che...mentioning
confidence: 99%